Preclinical immunogenicity and safety of a Group A streptococcal M protein-based vaccine candidate. Issue 12 (1st December 2016) - Batzloff, Michael R.; Fane, Anne; Gorton, Davina; Pandey, Manisha; Rivera-Hernandez, Tania; Calcutt, Ainslie; Yeung, Grace; Hartas, Jon; Johnson, Linda; Rush, Catherine M.; McCarthy, James; Ketheesan, Natkunam; et al.
ABSTRACT: Streptococcus pyogenes (group A streptococcus, GAS) causes a wide range of clinical manifestations ranging from mild self-limiting pyoderma to invasive diseases such as sepsis. Also of concern are the post-infectious immune-mediated diseases including rheumatic heart disease. The development of a vaccine against GAS would have a large health impact on populations at risk of these diseases. However, there is a lack of suitable models for the safety evaluation of vaccines with respect to post-infectious complications. We have utilized the Lewis Rat model for cardiac valvulitis to evaluate the safety of the J8-DT vaccine formulation in parallel with a rabbit toxicology study. These studies demonstrated that the vaccine did not induce abnormal pathology. We also show that in mice the vaccine is highly immunogenic but that 3 doses are required to induce protection from a GAS skin challenge even though 2 doses are sufficient to induce a high antibody titer.